2020
DOI: 10.1101/2020.10.02.20205641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of SARS-COV-2 Antibodies in Scottish Healthcare Workers

Abstract: Introduction: Healthcare workers are believed to be at increased risk of SARS-CoV-2 infection. The extent of that increased risk compared to the general population and the groups most at risk have not been extensively studied. Methods: A prospective observational study of health and social care workers in NHS Tayside (Scotland, UK) from May to September 2020. The Siemens SARS-CoV-2 total antibody assay was used to establish seroprevalence in this cohort. Patients provided clinical information including demogra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…5 In Scotland, hospital HCWs had a 3.4 times higher prevalence of SARS-CoV-2 antibodies than age-and sex-matched controls of general population (14.5% vs 4.8%). 20 In Wuhan, the attack rates among HCWs were 5.4 times higher than among non-HCWs. 21 Overall, 30% of other household members developed COVID-19-compatible symptoms, highly suggestive of COVID-19 given their epidemiological link with a laboratoryconfirmed case.…”
Section: Discussionmentioning
confidence: 98%
“…5 In Scotland, hospital HCWs had a 3.4 times higher prevalence of SARS-CoV-2 antibodies than age-and sex-matched controls of general population (14.5% vs 4.8%). 20 In Wuhan, the attack rates among HCWs were 5.4 times higher than among non-HCWs. 21 Overall, 30% of other household members developed COVID-19-compatible symptoms, highly suggestive of COVID-19 given their epidemiological link with a laboratoryconfirmed case.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the seroprevalence of SAR-CoV-2 IgG antibodies among healthcare workers was 1.2% in August and October 2020. It has been reported that the prevalence of SARS-CoV-2 antibodies in healthcare workers was higher than that in the general population (2,4). Our study also demonstrated that the prevalence of SARS-CoV-2 antibodies was relatively higher in healthcare workers than in the general population in Japan.…”
Section: Discussionmentioning
confidence: 91%
“…There is also mounting evidence that HCWs have a higher seroprevalence for SARS-CoV-2 antibodies than the general population, with a high proportion being asymptomatic. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%